Development and validation of an unsaturated soil water flow model for oil palm - Teh, Christopher Boon Sung (Universiti Putra Malaysia Press, 2018)
The development and use of a soil water model to predict the soil water flow and content under oil palm would be useful as a tool for more effective oil palm water management. Although many soil water models exist, none of them has been specifically developed, applied, and validated for oil palm. Consequently, the purpose of this study is to develop and validate such a model. Water flow was modelled following a one-dimensional "tipping bucket" system, and the soil profile was divided into several soil layers where the soil water and hydraulic characteristics for each layer were estimated based on the soil carbon content and soil texture. Darcy's law was applied to estimate the various soil water fluxes. The soil water model included algorithms to estimate the root water uptake and water stress response by oil palm. Raw data of measured soil water content for several soil depths (up to 90 cm) from two studies (Moraidi et al., 2015; Nur Farahin, 2013) were obtained, so that the accuracy of the soil water model could be validated by comparing simulations of soil water content with measured values. The model was satisfactorily accurate, showing similar daily trend as that observed for the measured soil water content. Goodness-of-fit indexes further indicated that the model simulations showed little to no overall model bias and with an average absolute prediction error of only 10%. Future work is to increase model accuracy by estimating the daily actual evapotranspiration instead as assumed constant in this study.